CLINICAL PROFILE AND OUTCOME OF VENTILATED CHILDREN IN A PEDIATRIC INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL - Javaid, Muhammad Sulman; Basheer, Faisal; Jalil, Jawad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the clinical profile and outcome of mechanically ventilated patients at a pediatric intensive care unit of a tertiary care teaching hospital of Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Pediatric Intensive Care Unit, Pak Emirates Military Hospital Rawalpindi, from Jan 2018 to Jun 2018. Methodology: A prospective study was conducted on 200 patients admitted in the pediatric intensive care unit. Demographic profile included age, gender, medical illness and reason to put on the ventilator. Duration for which each patient stayed on mechanical ventilations was also calculated. Outcomes included death, discharge from Intensive Care Unit and leave against medical advice (LAMA). Results: A total of 200 patients admitted in pediatric intensive care unit were put on ventilator in the study duration time. Respiratory tract diseases including pneumonia was the commonest underlying medical disorder among the target population followed by neurological disorders. Mean age of patients put on ventilator was 3.23years (± 4.945). Most of the patients were put on ventilator in gasping condition. Out of 200 patients, 110 (55%) died, 75 (37.5%) were discharged and 15 (7.5%) left against the medical advice (LAMA). Conclusion: This study gives an insight into the pattern of common illnesses and conditions encountered and managed in a pediatric intensive care unit. Management of critically ill children involving the mechanical ventilator is an integral part of pediatric critical care medicine. More expertise and depth in this aspect may improve the outcome among these critically ill children.